Crystal structure and Hirshfeld surface analysis of ethyl 2-{[4-ethyl-5-(quinolin-8-yloxymethyl)-4H-1,2,4-triazol-3-yl]sulfanyl}acetate - Rawia Imane Bahoussi; Ahmed Djafri; Abdelkader Chouaih; Ayada Djafri; Fodil Hamzaoui (Acta Crystallographica Section E: Crystallographic Communications, 2017)
In the title compound, C18H20N4O3S, the 1,2,4-triazole ring is twisted with respect to the mean plane of quinoline moiety at 65.24 (4)°. In the crystal, molecules are linked by weak C—H...O and C—H...N hydrogen bonds, forming the three-dimensional supramolecular packing. π–π stacking between the quinoline ring systems of neighbouring molecules is also observed, the centroid-to-centroid distance being 3.6169 (6) Å. Hirshfeld surface (HS) analyses were performed.